The Use of Hyperbaric Oxygen Therapy in the Management of Severe Radiation-Induced Hemorrhagic Gastritis in a Pediatric Patient. Issue 1 (3rd February 2022) - Rabinovich, Erica; Johnson-Arbor, Kelly; Serrano, Mariastella; Chao, Catherine; Eblan, Michael J.; Rao, Avani D.; Terao, Michael; Toretsky, Jeffrey; Sarangi, Susmita; Varela, Carly; Hong, Dahye
Abstract : Radiation-induced hemorrhagic gastritis is a serious and rare complication of radiation therapy. Optimal therapies in the pediatric population are not well established. We report a 2-year-old female diagnosed with rhabdomyosarcoma who developed hemorrhagic gastritis following chemotherapy and radiation therapy. The patient presented with acute onset anemia, hematemesis, and melena. Endoscopies revealed circumferential ulceration at the pylorus with spontaneous oozing that failed to respond effectively with multimodal medical and endoscopic therapies. Following hemodynamic stabilization, the patient was treated with hyperbaric oxygen therapy with excellent clinical response of the bleeding. Further research on the benefit of hyperbaric oxygen therapy is warranted to determine if this treatment can reduce the incidence of gastrointestinal complications in patients who have received radiation therapy.